HUMAN DEVELOPMENT ANALYSIS: THE ROLE OF DEMOGRAPHIC FACTORS IN WEST NUSA TENGGARA IN THE PERIOD OF 2013 - 2017 - PRADANA, FARRAS ADI (Jurnal Ilmiah Mahasiswa FEB, 2019)
The increasingly demands of globalization encourage various regions to compete in improving thewelfare of their people. One effort to achieve it is in the demographic sector, namely by improving thequality of Human Resources (HR). A good quality of HR will boost the pace of the HumanDevelopment Index (HDI), which is common indicator of the development of a region. West NusaTenggara Province which has a low HDI but has potential in its community. By utilizing the paneldata model, the analysis of this study took sample data from year 2013 to 2017, and aims to determinethe effect of demographic factors, namely population density, open unemployment, fertility and productive age as independent variables toward HDI as a dependent variable in West Nusa Tenggara. The empirical results of this study indicate that the population density variable has a positiveassociation on HDI while unemployment and fertility have a negative relationship on HDI in WestNusa Tenggara. Keywords : Human Resources (HR), HDI, demography, stunting, panel data